Ciência em tempos de Aids: uma análise da resposta pioneira de São Paulo à epidemia - França, Martha San Juan (2008)
This thesis aims to show how and why Brazil developed its internationally acclaimed model for fighting Aids. This model is based on Latin America s pioneer program, created in the Brazilian state of São Paulo in 1983, two years after the epidemic officially began in the United States. Based on reports by doctors and other healthcare professionals who started the São Paulo program, this study aims to present the ethical, political, and scientific references that gave rise to the Brazilian model for fighting AIDS and to show how these references have influenced the majority of public positions adopted in Brazil. The reports and complimentary research have shown how the ideas of the sanitary reform movement of the 1980s influenced the São Paulo program for fighting AIDS. This movement proposed the expansion and improvement of health coverage in Brazil, and, above all, an increase of public participation in matters related to health and illness. Given the period of history in which the epidemic appeared, in São Paulo it was possible to carry out a constructive dialogue between medicine and society, that is to say, between the creation of knowledge and the application of knowledge. Should this dialogue be furthered, it can serve as a tool to evaluate the role of science in the politics of health, and vice-versa, thus incorporating important social considerations into the scientific process of identifying options and making decisions. In this thesis, we aim to follow the methodology of the Simão Mathias Center / History of Science Post-Graduation Studies Program (Cesima/PEPGHC) of PUCSP. According to this methodology, the History of Science represents an opportunity to reflect upon and give context to multiple areas of knowledge today Natural Sciences and Human Sciences among them. Considering that the interests of these two areas have become more integrated, we have been able to explore aspects formerly neglected by Science History, such as the various institutions that intermediate between knowledge and society with the goal of showing how knowledge is produced, organized, and measured